Determination оf Optimum Constructive Parameters for Circulating-Reagent Regeneration Sector Apparatus - A. M. Sheiko; V. V. Ivashechkin; V. V. Veremenuk (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
On the basis of equation analysis for velocity distribution in near filter mudded zone optimal constructional parameters of sector apparatus for circulating-reagent well filter regeneration have been evaluated via angle ratio of forcing and section sectors and number of sectors. The method for determination of sector apparatus length of а selected pump that provides dissolution of mud formation in filter and near filter zone is proposed in the paper. The obtained data would promote upgrading of circulating-reagent water well regeneration technology and it permits to carry out high quality and even rehabilitation of pore space penetration along the full well filter length.